Diseño e implementación de un piloto de red wireless mesh basada en firmware libre utilizando nodos 802.11 en el A.E.I.R.N.N.R. de la Universidad Nacional de Loja. - Benítez León, María Fernanda (2018)
This document offers theoretical and techniques knowledges about Wireless Mesh Networks, the OLSR protocol, the OpenWrt firmware and WRT54GS Linksys routers version 3.0. The development of the project was made in several phases, first it was proceeded to choose the appropriate release of the firmware according to the version and techniques characteristics of the devices. Chosen the compatible release with the devices, it was installed in each one of them, as well as the demon of OLSR protocol with the necessary complements in order to its proper functioning. For the configuration of the network some previous factors were taken in account, like the channel, name of the network, HNA parameter among others, it was made the configurations LAN interfaces, WLAN, the firewall, and parameters of the protocol, it was got a graphic of the network through the installation of differents plugins. The prototype was implemented in Telecommunications Laboratory, and consists of 6 nodes, for the analyses of the protocol the tool Wireshark was used, with which was made the analyses of the traffic capture, allowing us to know the fields and information what the protocol handles in the control messages, furthermore it was taken the converged time of a new router to the network, and the time what network takes for calculate a new path when the node falls by the ping command. To analyze the viability of the network tests were performed which allowed us to analyze the impact of the number of hops in metrics such as the delay and transmission rate for which diagnostic tools such as ping, iperf and Wireshark were used. As a complementary part one simulation was made to know the behavior of the protocol in the network, the software chosen was NS3 because its contains examples about the OLSR protocol, the modified file was “olsr-hna”, in which was changed the number of routers and its spot; and it was proceeded to analyze the traffic capture of the simulation trough wireshark.